2021
DOI: 10.1002/smll.202103997
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Motion‐Activated Endogenous Wound Healing through LBL Self‐Powered Nanocomposite Repairer with pH‐Responsive Anti‐Inflammatory Effect

Abstract: infection from secondary stripping. In brief, as a pluripotential medical dressing sensor, the HAP/SN-NR has a promising future in various applications, especially tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 71 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…[32,33] New chemical shifts at 4.82, 4.99, and 5.09 ppm occurred in ODex due to the presence of aldehydes. [34,35] The covalent Schiff base network endows the hydrogel with excellent tissue adhesion capacity, [36,37] enabling the formation of a physical barrier to prevent bacterial invasion and maintain a moist environment to promote wound healing. [38] The hydrogel can strongly adhere to freely bent finger joints and twisted porcine skin (Figure 2b,c).…”
Section: Characterizations Of Odex/gc/mos 2 @Au@bsa Hydrogelsmentioning
confidence: 99%
“…[32,33] New chemical shifts at 4.82, 4.99, and 5.09 ppm occurred in ODex due to the presence of aldehydes. [34,35] The covalent Schiff base network endows the hydrogel with excellent tissue adhesion capacity, [36,37] enabling the formation of a physical barrier to prevent bacterial invasion and maintain a moist environment to promote wound healing. [38] The hydrogel can strongly adhere to freely bent finger joints and twisted porcine skin (Figure 2b,c).…”
Section: Characterizations Of Odex/gc/mos 2 @Au@bsa Hydrogelsmentioning
confidence: 99%
“…Benefit from the strong hygroscopicity and abundant internal space, chitosan-based hydrogels can also absorb contaminants from wound effusion. Further antimicrobial-enhanced chemical modification (such as quaternary ammonium, 30,35,[37][38][39][40][41][42][43] alkylate [44][45][46] and antibacterial peptide 41,47 ) and physical encapsulation (such as antibiotics, 31,32,45,47 polydopamine, 38,42,48 graphene oxide, 30,38,49 carbon nanotubes 50 and other nanomaterials 37,42,45,48,51 ) methods are also favorable.…”
Section: Chitosanmentioning
confidence: 99%
“…Smart hydrogel, with the identities of traditional hydrogel, could react to certain stimulus, e. g. temperature, enzyme or reactive oxygen species (ROS) [ [26] , [27] , [28] , [29] ]. Some researches indicated that smart hydrogel could heal the wound better due to its stimuli-responsive ability and drug delivery capacity [ [29] , [30] , [31] , [32] , [33] ]. These characteristics make smart hydrogel suitable for loading exosome.…”
Section: Introductionmentioning
confidence: 99%